Prarancangan Pabrik Bisphenol-A dari Phenol dan Aceton Kapasitas 20.000 Ton/Tahun - PERWITA, Alip Isnu Aji; , Kusmiyati, S.T, M.T, Ph.D; , Ir. Herry Purnama, M.T., Ph.D (2015)
In the era of technological advances in various fields of development was rapid, it would require some sort of infrastructure for the era of free competition. One of the prospects for future development is to build a factory that has competitiveness with foreign products. One of them is by establishing Bisphenol-A plant with raw materials Phenol and Aceton. with a capacity of 20,000 tons per year is planned to operate for 330 days per year. Acetone-making process is done in RATB reactor (CSTR). In the reactor the reaction at liquid-liquid phase, irreversible, exothermic, non-adiabatic, isothermal temperature 50C bait and a pressure of 1 atm. The factory is classified as low-risk plant operating conditions at atmospheric pressure. Phenol for this plant needs as much 3267.9482 kg per hour and needs as much Aceton 672.2501 kg per hour. Bisphenol-A products such as 2525.2525 kg per hour. Process support utilities includes water supply by 71555.9677 kg per hour were obtained from river water, the provision of 4928.2858 kg of saturated steam per hour compressed air requirement of 45.88 m3 per hour, the demand for electricity is obtained from the PLN and two generator sets of 400 kW in reserve, as much as 3.0034 liter of fuel per hour. The factory was established in Cilegon industrial area with a land area of 30,000 m2 and the number of employees 145 people. Bisphenol-A factory uses a fixed capital of Rp 35,354,439,981 and working capital of Rp 104 233 369 503. From the economic analysis of this plant show a profit before tax of Rp 61,657,094,694 per year after taxes 30% profit reached Rp 18,497,128,408 per year , Percent Return On Investment (ROI) before tax after tax of 22.672% and 15.870%. Pay Out Time (POT) before tax during the year and after tax 3.061 3.865 years. Break Even Point (BEP) of 59.4541%, and Shut Down Point (SDP) of 36.713%. From the data above feasibility analysis concluded that the plant is profitable and feasible to be established.